Konsep Pendidikan Islam Dalam Pembentukan Pribadi Kafah Menurut Ibnu Athaillah : Analisis Kitab Al-Hikam - Murtasyadatul Laili; Moch. Sya'roni Hasan (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2022)
This study aims to determine: 1. Islamic education according to Ibn 'Athaillah (analysis of the book of al-Hikam), 2. Islamic education materials according to Ibn 'Athaillah (analysis of the book of al-Hikam) and 3. Methods of forming the personality of kafah according to Ibn 'Athaillah ( analysis of the book al-Hikam). This research is a qualitative research, which belongs to the category oflibrary researchwith documentary data collection techniques. The data analysis technique was carried out using deductive methods and analytical methods. The results of the study stated that the concept of Islamic education according to Ibn Athaillah is to be comprehensive and balanced between the elements of shari'ah, tarekat and nature. Meanwhile, Islamic education material according to Ibn Athaillah in the book of wisdom is classified as covering aqidah material, worship material, mu'amalah material, moral material, material about the heart, social material, and intellectual/reasonable material. And the method of forming a personal kafah according to Ibn Athaillah in the book of wisdom has been classified, including: the graduation method, the dialogue method, the dhikr method, the method of advising and reminding, the equation method, the causal method, the motivating method. The similarity of the concept of Islamic education with Ibn Athaillah is that development includes the worldly-ukhrawi, physical-spiritual dimensions and all aspects of life, both those that can be reached by reason and those that are only believed through the heart, not only on the outward side, but inwardly, and the ultimate goal has a personality. main. The materials and methods of Islamic education used are sourced from the Al-Quran and Hadith.